The effect of ESD-based problem based learning on grade 10 students’ critical thinking skills and sustainability awareness - Anggi Yusriana; Yuni Ahda; Heffi Alberida; Reki Kardiman (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
21st-century learning requires students to develop critical thinking skills and sustainability awareness to address global challenges. Initial observations indicated that students’ critical thinking skills ranged from less critical to moderately critical, while sustainability awareness was moderate. This study investigated the effect of ESD-based Problem-Based Learning (PBL) on these two outcomes among Grade 10 students at SMA Pertiwi 1 Padang. A quasi-experimental posttest-only control group design was employed, involving an experimental group receiving ESD-based PBL and a control group receiving the regular learning approach. Data were collected using a critical thinking essay test and a sustainability awareness questionnaire and analyzed using MANOVA. The results showed a significant multivariate effect (Wilks’ Λ = 0.285, F(2,62) = 77.707, p < 0.001, η²p = 0.715). Univariate analysis showed significant effects on critical thinking skills (F = 152.873, p < 0.001, η²p = 0.708) and sustainability awareness (F = 10.633, p = 0.002, η²p = 0.144). The experimental group obtained higher mean scores for critical thinking (78 vs. 52) and sustainability awareness (79 vs. 72). These findings indicate that ESD-based PBL was associated with higher critical thinking skills and sustainability awareness, although the findings are limited to immediate post-intervention outcomes.